Identification of Glutathione Peroxidase Gene Family in Ricinus communis and Functional Characterization of RcGPX4 in Cold Tolerance - Wang, Xiaoyu; Liu, Xuming; An, Yong-qiang Charles; Zhang, Hongyu; Meng, Di; Jin, Yanan; Huo, Hongyan; Yu, Lili; Zhang, Jixing (Frontiers in Plant Science, 2021)
Glutathione peroxidases (GPXs) protect cells against damage caused by reactive oxygen species (ROS) and play key roles in regulating many biological processes. Here, five GPXs were identified in the Ricinus communis genome. Phylogenetic analysis displayed that the GPXs were categorized into five groups. Conserved domain and gene structure analyses showed that the GPXs from different plant species harbored four highly similar motifs and conserved exon-intron arrangement patterns, indicating that their structure and function may have been conserved during evolution. Several abiotic stresses and hormone-responsive cis-acting elements existed in the promoters of the RcGPXs. The expression profiles indicated that the RcGPXs varied substantially and some RcGPXs were coordinately regulated under abiotic stresses. Overexpression of RcGPX4 in Arabidopsis enhanced cold tolerance at seed germination but reduced freezing tolerance at seedlings. The expression of ABA signaling genes (AtABI4, AtABI5), ABA catabolism genes (AtCYP707A1, AtCYP707A2), GA catabolism gene (AtGA2ox7), and cytokinin-inducible gene (AtARR6) was regulated in the seeds of transgenic lines under cold stress. Overexpression of RcGPX4 can disturb the H2O2 homeostasis through the modulation of some antioxidant enzymes and compounds involved in the glutathione-ascorbate cycle in transgenic plants. Additionally, RcGPX4 depended on the MAPK3-ICE1-CBF-COR signal transduction pathway and ABA-dependent pathway to negatively regulate the freezing tolerance of transgenic plants. This study provides valuable information for understanding the potential function of RcGPXs in regulating the abiotic stress responses of castor beans.